Examining the Degree of Changes in Korean Elementary Schools' Physical Activity Promotion System Grades amidst the COVID-19 Pandemic - Byung-Kweon Chang (Tehran University of Medical Sciences, 2022)
Background: The study aimed to provide basic data about the changes in the Korean elementary schools' Physical Activity Promotion System (PAPS) amidst the COVID-19 pandemic and to present future direction for school and physical education. Methods: Data were collected for 2019-2021 from the PAPS, conducted by the Korea Ministry of Education. Participants were fifth and sixth level students from 1,214 Korean elementary schools, with 124,871, 126,396, and 117,953 participants in 2019, 2020, and 2021, respectively. Five physical fitness variables were evaluated-cardiopulmonary endurance, flexibility, muscle strength, power, and obesity-and graded from 1 (highest physical fitness level) to 5 (lowest physical fitness level). Data were analyzed using repeated measures analysis of variance and Bonferroni for multiple comparisons for computing confidence intervals. Results: The findings indicated significant changes in the ratios of grades 1, 2, 4, and 5 according to the year (P<0.05). Grades 1 and 5 decreased and increased in 2021 from 2019 and 2020, respectively (P<0.001). Grades 2 and 4 continuously decreased and increased from 2019 to 2020 (P=0.001, P<0.001, respectively) and further in 2021 (P<0.001), respectively. Moreover, significant changes were identified in the grade ratio by year according to sex (P<0.05). Male students reported higher grade 1 ratios than female students in 2019 (P=0.018) and 2021 (P<0.001). However, for all 3 years, female students reported higher grade 2 ratio (P<0.001), while male students reported higher grade 4 and 5 ratios (P<0.001). Lastly, male students reported higher grade 3 ratios than female students in 2019 (P=0.003), but this finding was reversed in 2021 (P=0.004). Conclusion: The pandemic decreased students' physical activity and weakened their health, and this reduced fitness was greater pronounced in male students. In the future, physical educators should plan and present solutions to tackle reduced physical activity post the pandemic.